Penerjemahan Parikan Jawa Bahasa Indonesia sebagai Sumber Pembelajaran Kajian Linguistik Fungsional Sistemik - Mayasari; Zuindra; Misla Geubrina; Muhizar Muchtar; Wan Anayati (Universitas Negeri Medan, 2026)
This study is motivated by the importance of understanding interpersonal meaning in the translation of cultural texts, particularly Javanese parikan, which encompasses not only linguistic aspects but also social and cultural values. The study aims to analyze interpersonal meaning variation in the translation of Javanese parikan into Indonesian using the Systemic Functional Linguistics approach and to examine its implications for language learning. This research employs a descriptive qualitative method with data sourced from parikan in the book Parikan-Pantun Jawa. The sample consists of 100 clauses selected through purposive sampling. Data analysis focuses on identifying mood and residue structures to examine interpersonal meaning shifts between source and target texts. The findings reveal that low variation dominates at 62%, followed by moderate variation at 25% and high variation at 13%. These results indicate that most interpersonal structures in the source text are preserved in the translation due to the grammatical similarities between Javanese and Indonesian. Furthermore, the study shows that parikan can be utilized as a contextual learning resource, as it helps students understand the relationship between linguistic structure and social function. Therefore, the Systemic Functional Linguistics approach is not only effective for translation analysis but also relevant for developing culturally based language learning.